KAJIAN DIAMETER - PERSENTASE KAYU TERAS TERHADAP KUALITAS KAYU JATI (Tectona grandis Linn. F) DARI HUTAN RAKYAT GUNUNG KIDUL - Woesono, Hastanto Bowo (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2011)
The research is aim to determine of influence diameter and percentage heartwood to physical and mechanical of teakwood properties. This research uses wood diameter factor, which comprises 3 levels of 15-21 cm, 22-28 cm and 29-35 cm and the percentage of heartwood that comprises 3 levels of 25-45%, 45-65% and 65-85%. These factors were then designed a randomized complete with factorial pattern. Observed parameters are the physical properties of wood (moisture content, specific gravity, and dimensional changes) and the mechanical properties of wood (static bending strength, compression strength parallel to grain, compression strength perpendicular to grain and shear strength). The result of the research shows that diameters factor affect significantly on air dry moisture content, longitudinal shrinkage from air dry to oven dry condition, Modulus of Elasticity (MOE) and compression strength parallel to grain. The percentage of heartwood factor affects very significantly on moisture content, tangential swelling from air dry to wet condition and Modulus of Elasticity. The interaction factor between diameters and percentage of heartwood also affects very significantly on specific gravity and shear strength. The rate of air dry moisture content is 13.88%; specific gravity is 0.65; MOE is 108.13 (1000kg/cm2); MOR is 1243.83 kg/cm2; compression strength parallel to grain is 569.41 kg/cm2; compression strength perpendicular to grain is 122.80 kg/cm2; and shear strength is 79,1602 kg/cm2. The result of the research show also that wood has the highest diameters is not always the best of quality (physical and mechanical properties) but, the highest percentage of heartwood to trend has the better teakwood quality specially physical properties. Key Words : diameters, the percentage of heartwood, community forest teakwood quality